A Representation of Multicultural Values in the Novel Si Anak Pemberani by Tere Liye - Ahmad Fajrul Falah; Mukhzamilah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the representation of multicultural values in the novel Si Anak Pemberani by Tere Liye. The focus of the study is directed at four aspects of multicultural values, namely (1) solidarity and social brotherhood, (2) gender equality, (3) family values, and (4) respect for morals. This research uses a type of qualitative research with a literary anthropology approach. The source of research data is in the form of the novel Si Anak Pemberani by Tere Liye, while the research data is in the form of narrative quotes and dialogues that represent multicultural values. Data collection techniques are carried out through reading, listening, recording, and literature study techniques. Data analysis was carried out using a hermeneutic method to interpret the meaning of multicultural values contained in novel texts. The results of the study show that the novel Si Anak Pemberani represents the value of solidarity and social brotherhood through the attitude of mutual cooperation and the collective struggle of the village community in defending the environment. The value of gender eqity is displayed through the character of Eliana who is courageous, critical, and active against injustice. Family values are illustrated through harmonious relationships between family members and the community based on mutual care. Meanwhile, the value of respect for morals is reflected in respect for parents, self-control, and compliance with religious and social norms. Based on the results of the research, it can be concluded that the novel Si Anak Pemberani not only functions as a children's literary work, but also as a medium of character education that instills multicultural values in the life of a pluralistic society.